Keynote: ILRI research on foodborne diseases associated with pigs - Grace, Delia; Hung Nguyen-Viet (International Livestock Research Institute, 2019)
This keynote was prepared by Delia Grace, ILRI program leader of Animal Human Health and presented by Hung Nguyen, ILRI regional representative for East and Southeast Asia at the Regional Symposium on Research into Smallholder Pig Production, Health and Pork Safety. The Symposium was co-hosted by the International Livestock Research Institute (ILRI) and the University of Queensland, Australia, with the support from the Australian Centre for International Agricultural Research (ACIAR) and the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH). The meeting was held in Vietnam from 27-29 March 2019.